Efeitos da fotobiomodulação associada com a fisioterapia no desempenho funcional de crianças com mielomeningocele- estudo clínico, randomizado e cego - Silva, Tamiris da (2022)
Myelomeningocele is a neural tube defect that occurs during embryonic development due to the incomplete closure of the spinal neural tube. It ultimately leads to an exposed neural tissue or meninges with a fluid-filled sac that protrudes at the affected vertebral level. The unprotected neural tissues suffer progressive harm due to exposure to chemical and mechanical factors of the intrauterine environment. These impairments may impact the child's functionality, placing them at risk for decreased social participation. Physiotherapy is an important feature of the rehabilitation of individuals with MMC. However, knowledge of which physiotherapeutic strategies should be used or the best frequency and intensity of the sessions are still lacking. of photobiomodulation (PBM) as a supplemental therapeutical tool has demonstrated positive effects in sensory and motor recovery patients with spinal cord injuries when combined with physiotherapy or alone in in vivo spinal cord injury models. Purpose: Evaluate the effects of PBM associated with physiotherapy on the functional performance of children with myelomeningocele. Methods: Twenty-five children were randomly allocated to either Active PBM+physiotherapy (n = 13) or PBM sham+physiotherapy (n = 12). PBM was carried out with a LED device (850 nm, 25 J, 50s per point and 200 mW) at four points over the area with absence of a spiny process. Both groups completed twelve-week supervised program with two weekly 45 – 60 min sessions. Pre-training and post-training assessments involved the Pediatric Evaluation of Disability Inventory (PEDI score). Muscle activity was assessed using portable electromyography (BTS Engineering) and the electrodes were positioned on the: lateral gastrocnemius, anterior tibialis and rectus femoris muscles. Results: After 24 sessions of the treatment protocol, improvements were found in the PEDI score in both evaluated groups. The participants presented greater independence in performing the tasks, requiring less assistance from their caregivers. More significant electrical activity was found in the three muscles evaluated between the rest period and execution of the sit-to-stand tasks, both in the more compromised or less compromised lower limbs. Conclusion: Neurofunctional physiotherapy with or without PBM improved functional mobility and electrical muscle active in children with myelomeningocele.